DEPRESSION, GENDER AND PATRIARCHY: A PSYCHOLOGICAL READING OF THE PROTAGONIST IN CHO NAM-JOO’S KIM JI-YEONG, BORN 1982 - Andang Suhendi; Yaumil Titi Faila Lubis; Zulfan Sahri (JOURNAL OF LANGUAGE, 2025)
This article investigates the forms and causes of depression experienced by the protagonist in Cho Nam-Joo’s novel Kim Ji-Yeong, Born 1982, situating the narrative within the intersection of psychology, gender studies, and feminist literary criticism. Drawing on Bhowmik et al.’s (2012) framework of depression, the study applies a qualitative descriptive method to examine the protagonist’s psychological decline, which unfolds through three stages: baby blues, postpartum depression, and postpartum psychosis. Textual analysis reveals that Ji-Yeong’s condition is triggered by sleep disturbances, stressful life events, and the forced resignation from her professional career. These immediate causes, however, are embedded within broader patriarchal structures that regulate women’s identities and diminish their autonomy. The findings underscore that Ji-Yeong’s depression is not merely an individual pathology but a cultural and political condition shaped by systemic gender inequality. The novel dramatizes how patriarchal surveillance, misogyny, and intergenerational trauma exacerbate women’s mental health struggles. By portraying Ji-Yeong’s breakdown as both personal and collective, Cho Nam-Joo transforms literature into a form of feminist critique. This article contributes to literary psychology by demonstrating how fiction can illuminate the sociocultural dimensions of depression, offering insights that extend beyond psychiatry into the realm of social justice.